Analisis Docking Molekuler Ligand Fitokimia terhadap Protein 1ND2 Rhinovirus - Rahma Dika Aulia Nasution; Deski Beri (Lembaga Yasin AlSys, 2026)
Although rhinovirus has a high prevalence worldwide, the development of antiviral agents specific to this virus remains limited. This study aims to evaluate phytochemical compounds from Indonesian medicinal plants as potential antiviral candidates against rhinovirus. This study used a quantitative in silico approach through molecular docking using MOE 2022 to analyze the interactions between 13 ligands and the target protein 1ND2. The results showed that tannin (-10.2962), cowanol (-8.9288), and zanthoxylin (-7.4879) had the best binding affinities compared with the other ligands. These findings indicate that phytochemical compounds have the potential to be developed as plant-based antiviral agent candidates. This study contributes to the development of ethnobotany-based drug discovery research and provides an initial basis for further experimental validation. Thus, the exploration of phytochemical compounds from Indonesian medicinal plants has important implications for the development of antiviral therapeutic candidates that are more specific to rhinovirus.